Modeling of Frost Formation on Fin-and-Tube Surface of Air Cooler - Lagutin A. E.; Kozachenko I. S.; Zheliba U. A. (Problems of the Regional Energetics, 2017)
The aim of this paper is to present a new method of modeling of frost predicting process on the surface of the fine-and-tube air cooler. The advantage in comparison with existing similar models is a significant reduction in the number of operations performed to determine the optimal geometrical parameters of the heat exchange surface. In this paper presented structural scheme of mathematical model, described benefits and usage area. The study present the results of numerical modeling for ammonia air cooler with staggered tube bank and injection molding round fins. The model tested on range of values: coolant temperature (t0= –20, –27°C), temperature difference between coolant and ambient air (θ=7, 10°C), relative humidity (φ=90…98%), air velocity (w=3, 5, 7 m/s). Fin spacing permitted δ=10mm. The result of study shows the effect of the above parameters on the frost formation dynamic and frost distribution on tube rows along air flow. Presented program application allows providing improving of fin-and tube air cooler due to fin spacing optimization. Consequently heat exchange surface redistribute and increase on the area of maximum efficiency.